E-COMMERCE: THE IMPORTANCE ROLE OF CUSTOMER PERCEIVED VALUE IN INCREASING ONLINE REPURCHASE INTENTION - Prasetyo, Johan Hendri; Prakoso, Bobby Suryo; Wiharso, Gani; Fabrianto, Luky (Dinasti Publisher, 2021)
In the midst of digital business growth rapidly and Covid-19 pandemic that has lasted for several years, people tends to carry out all their activities from home, including fulfilling their needs through various e-commerce services. This research model intends to investigate the important role from customer perceived value in increasing online repurchase intention on various e-commerce sites in Indonesia, such as Shopee, Tokopedia, Bukalapak, Lazada and Blibli. This research method designed by quantitative causality with a total sample of 310 people through snowball sampling. The analytical method used AMOS-SEM to verified the role of customer value perceptions. This results shows that customer perceived value indirectly act as an crucial part in increasing the influence from e-service quality, ease of use, store image and online promotion on online repurchase intention.